New Trends in International Law : Festschrift in Honour of Judge Hisashi Owada - Chia-Jui Cheng, (International Law E-Books Online, Collection 2024., 2024)
The Festschrift New Trends in International Law is a collective work which reflects the contributions of Judge Owada to the development of international law, and also deals with various issues of modern international law which have been challenged by the third world. The contributors are jurists from the ICJ and ILOS whose judgments and advisory opinions constitute the formal sources of modern international law. New Trends in International Law also presents contributions from a number of the most highly qualified scholars of various nations whose specialisations are frequently adopted as material sources of international law New Trends in International Law is an invaluable resource for modern international law which provides the entire spectrum of its evolution and its key challenges. It provides an ideal reference source for students, post-graduate researchers, practitioners, functionaries of international institutions, as well as government officials in charge of foreign affairs.